Glycosphingolipids of porcine blood: human blood group A and H antigens with type 1 chain in erythrocytes and plasma - Makita, A; Gasa, S; Sako, F; Hanagata, G (Indian journal of biochemistry & biophysics, 1990)
Glycosphingolipids were purified from porcine erythrocytes and plasma. Two minor glycolipids with human blood group A and H antigenicities were found in both sources as components. The two antigenic glycolipids were identified as a hexaglycosylceramide (IV3 alpha GalNAc,IV2 alpha Fuc-Lc4Cer) for the A antigen and pentaglycosylceramide (IV2 alpha Fuc-Lc4Cer) for the H antigen and belonged to lactoseries (type 1 sugar chain) in contrast to those with neolacto core (type 2 sugar chain) in human erythrocytes, thereby endorsing biochemically the previous serological observations that the A antigen on porcine erythrocytes is uptake from plasma, probably the H antigen being the case. In addition to major glycolipids of globoseries in red cells and plasma, a variety of acidic glycolipids including two classes of sulphatides (sulphated galactosylceramide and sulphated lactosylceramide) and five classes of gangliosides (GM3, GD3, GM1, fucosyl GM1 and GD1a) containing N-acetylneuraminic acid and N-glycolylneuraminic acid were obtained from plasma.